A Single Supratherapeutic Dose of Atogepant Does Not Affect Cardiac Repolarization in Healthy Adults: Results From a Randomized, Single‐Dose, Phase 1 Crossover Trial. Issue 9 (4th May 2021) - Boinpally, Ramesh; McNamee, Brian; Yao, Li; Butler, Matthew; McGeeney, Danielle; Borbridge, Lisa; Periclou, Antonia
Abstract: Atogepant is a selective, oral calcitonin gene–related peptide receptor antagonist in development for preventive treatment of migraine. This randomized, double‐blind, phase 1 crossover study evaluated the cardiac repolarization effect of a single supratherapeutic (300 mg) atogepant dose vs placebo in healthy adults. Moxifloxacin 400 mg was the open‐label active control. The primary end point was a change from baseline in Fridericia‐corrected QT intervals (ΔQTcF). Sixty participants were randomized to atogepant 300 mg, placebo, and moxifloxacin; 59 (98.3%) completed all interventions. Assay sensitivity was confirmed: lower 90% confidence interval limit for QTcF interval change from baseline (ΔΔQTcF) for moxifloxacin was >5 millisecond vs placebo at prespecified 2‐, 3‐, and 4‐hour time points. Following single‐dose atogepant 300 mg, mean atogepant ΔΔQTcF and upper 90% confidence interval limits were lower than the 10‐millisecond threshold at all time points. Atogepant mean peak plasma concentration was 3197 ng/mL, area under the concentration‐time curve from time 0 to time t was 16 640 ng h/mL, area under the concentration‐time curve from time 0 to 24 hours was 16 607 ng h/mL, and median time to peak plasma concentration was 2.1 hours. The incidence of adverse events was low; no serious adverse events or elevations of liver enzymes were reported. Overall, a single supratherapeutic dose of atogepant was safe and did not impact cardiac repolarization in healthy participants.